Gas6 is a reciprocal regulator of mitophagy during mammalian oocyte maturation - Kim, Kyeoung-Hwa (Sci Rep, 2019)
Previously, we found that the silencing of growth arrest-specific gene 6 (Gas6) expression in oocytes impairs cytoplasmic maturation through mitochondrial overactivation with concurrent failure of pronuclear formation after fertilization. In this study, we report that Gas6 regulates mitophagy and safeguards mitochondrial activity by regulating mitophagy-related genes essential to the complete competency of oocytes. Based on RNA-Seq and RT-PCR analysis, in Gas6-silenced MII oocytes, expressions of mitophagy-related genes were decreased in Gas6-silenced MII oocytes, while mitochondrial proteins and Ptpn11, the downstream target of Gas6, was increased. Interestingly, GAS6 depletion induced remarkable MTOR activation. Gas6-depleted MII oocytes exhibited mitochondrial accumulation and aggregation caused by mitophagy inhibition. Gas6-depleted MII oocytes had a markedly lower mtDNA copy number. Rapamycin treatment rescued mitophagy, blocked the increase in MTOR and phosphorylated-MTOR, and increased the mitophagy-related gene expression in Gas6-depleted MII oocytes. After treatment with Mdivi-1, a mitochondrial division/mitophagy inhibitor, all oocytes matured and these MII oocytes showed mitochondrial accumulation but reduced Gas6 expression and failure of fertilization, showing phenomena very similar to the direct targeting of Gas6 by RNAi. Taken together, we conclude that the Gas6 signaling plays a crucial role in control of oocytes cytoplasmic maturation by modulating the dynamics and activity of oocyte mitochondria.